Hematopoietic stem cell transplantation - Eleftheria Hatzimichael (Dove Medical Press, 2010)
Eleftheria Hatzimichael1, Mark Tuthill21Department of Haematology, Medical School of Ioannina, University of Ioannina, Ioannina, Greece; 2Department of Medical Oncology, Hammersmith Hospital, Imperial College National Health Service Trust, London, UKAbstract: More than 25,000 hematopoietic stem cell transplantations (HSCTs) are performed each year for the treatment of lymphoma, leukemia, immune-deficiency illnesses, congenital metabolic defects, hemoglobinopathies, and myelodysplastic and myeloproliferative syndromes. Before transplantation, patients receive intensive myeloablative chemoradiotherapy followed by stem cell “rescue.” Autologous HSCT is performed using the patient’s own hematopoietic stem cells, which are harvested before transplantation and reinfused after myeloablation. Allogeneic HSCT uses human leukocyte antigen (HLA)-matched stem cells derived from a donor. Survival after allogeneic transplantation depends on donor–recipient matching, the graft-versus-host response, and the development of a graft versus leukemia effect. This article reviews the biology of stem cells, clinical efficacy of HSCT, transplantation procedures, and potential complications.Keywords: hematopoietic stem cell transplantation, complications